Effect of Foliar Nutrition on Uptake of Nutrients and Economics of Soybean - Paikra, Indrapal Singh; Lakpale, R.; Singh, Paramjeet; Kumar, Vijay (International Journal of Bio-resource and Stress Management, 2018)
A field experiment was conducted during kharif season of 2015 at the Research cum Instructional Farm, Indira Gandhi Krishi Vishwavidyalaya, Raipur to evaluate the effect of foliar nutrition on uptake of nutrients and economics of Soybean [Glycine max (L.) Merrill] under Vertisols of Chhattisgarh plains. The experiment was laid out in Randomized Block Design with three replications. The results revealed that application of RDF+spray of DAP @ 2% at pod initiations stages of crop growth resulted significantly higher uptake of nutrients N, P, K, and also positive effect on micronutrients and economics compared to the application of RDF+Water spray at pod initiation stage and RDF only. It also positive effect on micronutrients in soil such as activity of microbial population, improve seed quality and oil quality of soybean through regulate nutrient during pod filling stage when the soil are not able to provide nutrients, quality parameters and nutrient uptake of soybean were significantly influenced by foliar application of nutrients at different stages of crop. The foliar application of RDF+spray of DAP @ 2% recorded significantly higher net return of ` 60,279 with. B:C ratio of 3.07. Foliar spraying with 2% DAP at flowering and at early pod development in addition to soil application of NPK fertilizer was found to be more beneficial to improve the productivity of soybean than RDF application alone.